Critical Issues in Climate Change Science - Le Quéré, Corinne; Liss, Peter; Forster, Piers (Zenodo, 2021)
A collection of ScienceBrief Reviews synthesising the latest research on climate change impacts, understanding and future developments. This collection brings ScienceBrief Reviews together in one volume covering the impacts of climate change on wildfires, cyclones, extreme rainfall, marine heatwaves, Arctic amplification, carbon sinks and the role of independent expert advisory bodies. The evidence discussed in these reviews was collected at ScienceBrief.org and can be explored via links within each review.